Prosedur Pelaksanaan Lelang Di KPKNL Kanwil Banjarmasin Perspektif Hukum Ekonomi Syariah - Muhammad Iqbal; Anwar Hafidzi; M. Hanafiah (Indonesian Journal of Islamic Jurisprudence, Economic and Legal Theory, 2023)
Abstract This study aims to understand the procedures for implementing auctions at the KPKNL Regional Office of Banjarmasin sharia economic law perspective, as well as understanding how Islamic law views the implementation of these auctions and helps Muslim communities understand what auctions are like in the spirit of Islam. to better understand. Auctions in Islam are generally allowed as long as the auction is carried out with the pillars, the conditions are met, and there is no injustice. Although some scholars prohibit the auction, the majority of scholars are of the opinion that it is permissible to conduct the auction. The method used in this research is qualitative method. Data collection is done by interview, observation, and documentation techniques conducted by researchers. The implementation of the Banjarmasin Regional KPKNL auction in 2023, the Banjarmasin Regional KPKNL implemented a security deposit system and a limit value to avoid the practice of Najasy and Tadlis to ensure that the implementation of the Banjarmasin KPKNL auction was carrout in accordance with Islamic law review. Keywords: Auction, Law, Knowledge Abstrak Penelitian ini bertujuan untuk memahami prosedur pelaksanaan lelang di KPKNL Kanwil Banjarmasin dalam perspektif hukum ekonomi syariah, serta memahami bagaimana pandangan hukum Islam terhadap pelaksanaan lelang tersebut dan membantu masyarakat muslim memahami seperti apa lelang dalam semangat Islam. untuk lebih memahami pelelangan, dalam Islam pada umumnya diperbolehkan sepanjang pelelangan dilakukan dengan rukun, syarat-syaratnya terpenuhi, dan tidak ada kezaliman. Meskipun sebagian ulama melarang pelelangan, namun mayoritas ulama berpendapat boleh melakukan pelelangan tersebut. Metode yang digunakan dalam penelitian ini adalah metode kualitatif. Pengumpulan data dilakukan dengan teknik wawancara, observasi, dan dokumentasi yang dilakukan oleh peneliti. Penyelenggaraan lelang KPKNL Kanwil Banjarmasin, KPKNL Kanwil Banjarmasin menerapkan sistem uang jaminan dan nilai limit untuk menghindari praktik Najasy dan Tadlis guna memastikan pelaksanaan lelang dilakukan sesuai dengan tinjauan hukum Islam. Kata Kunci: Lelang, Hukum, Pengetahuan